Emerging market exchange rate exposure - Chue, Timothy K.; Cook, David (Journal of Banking & Finance, 2008)
We estimate the exposure of emerging market companies to fluctuations in their domestic exchange rates. We use an instrumental-variable approach that identifies the total exposure of a company to exchange rate movements, yet abstracts from the influence of confounding macroeconomic shocks. In the sub-period of 1999–2002, we find that depreciations tend to have a negative impact on emerging market stock returns. In the sub-period of 2002–2006, this tendency has largely disappeared. Since we estimate the exchange rate exposure of firms from different countries with a common set of instruments, we can make coherent, cross-country comparisons of their determinants. We find that the impact of various measures of debt on exchange rate exposure, which is negative and significant in the early sub-period, becomes insignificant and even reverses sign in the recent sub-period.